The Meaning of Technology Company Slogans: A Semantic Study - Isfahany Sarah Syahida; Hendar Hendar (Jurnal Sinestesia, 2023)
Technology company advertisement is becoming more and more creative and competitive as it has created certain public images of the companies through the use of slogans, which also have an impact on how the businesses are run. The aims of this research are to classify the types of meaning in technology company slogans and to find the purposes of the slogans. The seven types of meaning by Leech (1990) serves as the primary theory in this research. The method of this qualitative research is descriptive method; meanwhile, the method used to get the data needed on the purposes of slogans used by technology companies is documentary method as they are collected from their official websites and news websites. The results of the research shows that dealing with the types of meaning, it is found that there are only four types of meaning used by technology companies; conceptual meaning (25%), connotative meaning (12.5%), affective meaning (37.5%), and reflected meaning (25%); whereas, the purposes of the slogans used consist of increasing brand awareness (12.5%), promoting excellence (37.5%), conveying positive outlook (25%), and building social engagement (25%).